Role of Climate-Smart Agriculture in Enhancing Farmers' Livelihoods and Sustainable Forest Management: A Case of Villages Around Songe-Bokwa Forest, Kilindi District, Tanzania - Nkumulwa, Hamza Omary; Pauline, Noah Makula (Frontiers in Sustainable Food Systems, 2021)
Climate change and variability are happening in Tanzania, and their impacts are felt in the socioeconomic sectors, as they have resulted in the decline of agricultural productivity and increased deforestation. This study assessed the actual changes in deforestation levels and improved livelihoods caused by the adoption of climate-smart agriculture (CSA) practices. Data were collected through semi-structured household questionnaires, focus group discussions, key informants, GIS tools, and observations. Quantitative data were analyzed using Arc GIS 10.3 software, SPSS version 16.0, and Excel Spreadsheet, while qualitative data were analyzed through content analysis techniques. The findings show that farmers' livelihoods have improved and also deforestation levels decreased as a result of increased adoption of CSA during the past 30 years. Deforestation levels have been reduced from 64.6 ha per year during 1985–1995 to 11.8 ha per year during 1995–2005 and to 10.4 ha per year during 2005–2017. Further findings showed that the agricultural area had been decreased from 4,534 ha in 1995 to 4,039 ha in 2017, which is evidence that after the scale-up of CSA from the year 1992, agricultural practices were not contributing much to deforestation, while increased crop production and income were observed, which in turn supported farmers in enhancing food security, purchasing production tools, livestock, and payment for medical services, school fees, and construction of modern houses. We found that adoption of CSA systems such as agroforestry (i.e., agrisilviculture) is very crucial for improving farmer's livelihoods and reducing deforestation. Therefore, farmers need close mentoring on climate-resilient agroforestry systems, such as agrisilviculture.